The development and standardization of a group screening audiometer and procedure for Indian condition - MG, Kalai Selvan (Journal of All India Institute of Speech and Hearing, 1979)
Auditory screening is an attempt to identify persons who have significant hearing defects from a population made up predominently of people with normal or adequate hearing. The technique of screening is as it is purpose the identification as quickly as economically as possible and individuals in a large population who are in need of some special service